Validity of Random Triglyceride Levels in Infants Receiving Parenteral Nutrition - Bader, Mohammad Y.; Lam, Melanie A.; Munoz, Fernando; Thompson, Leslie; Kylat, Ranjit I. (Frontiers in Pediatrics, 2021)
Background: Intravenous lipid emulsions (IL) are an important part of PN to meet essential fatty acid (EFA) requirements and meet metabolic demands in neonates and preterm infants. Some critically ill neonates may not be able to metabolize the IL and can acutely develop hypertriglyceridemia. This can potentially increase pulmonary vascular resistance, displace bilirubin and cause platelet and macrophage dysfunction. Serum triglyceride (TG) concentration is used as a marker for lipid tolerance and predictor of potential complications involved with IL administration. But the clinical significance of this is still debated. Management of TG levels by timing of laboratory tests, the ideal goal range and duration of infusion of IL varies and is not standardized Methods: Single center non-randomized prospective study of newborn infants receiving parenteral nutrition (PN). Fasting and non-fasting TG levels were drawn during the same lipid infusion of 2-3g/kg/day. The primary outcome was the difference between fasting and non-fasting TG levels. Statistical assessment of continuous data was done with student t-test and nominal data were evaluated using X2-test and logistic regression. Results: 40 patients were included. The mean fasting TG level was significantly lower than the non-fasting level, however, this did not change management as the threshold TG level (250mg/dL) was reached only once in each of the groups. Conclusion: We concluded there is no difference in management when TG level was drawn randomly or as fasting sample. Obtaining TG level during routine testing is appropriate. We extrapolated that the administration of IL over 24 hours will not interfere with TG level.